Development of Ultraviolet Protective Fabric with Natural Herb - Sandeep Kidile (International Journal of Engineering and Management Research, 2019)
Effective textiles are a part of technical textiles that are defined as comprising all those textile-based products that are used principally for their performance or functional characteristics rather than their aesthetic or decorative characteristics. protective clothing is specially designed for sun protection and generally produced from the fabric rated for its level of ultraviolet (UV) protection. Ultraviolet rays constitute a very low fraction of the solar spectrum but influence all leaving organism. The sun is the principal source of UV exposure for most people. Exposure to the sun is known to be associated with various skin diseases, skin cancers, accelerated skin aging and other eye diseases, and probably has an adverse effect on persons ability to resist infectious diseases. The rating system of fabric specifies an ultraviolet protection factor (UPF) value, which can be thought as a time factor for the protection of Caucasian skin compared to exposure without exposure without any protection from sun's UV as a means of protecting skin from damage. The shorter the wavelength, the higher the energy of radiation.UVA rays account for 90 to 95% of UV radiation that reaches the earth. While UVB makes only 5 to 10% of solar radiation, its high-energy damages surface epidermal layers and cause sunburn.UVB is strongest particularly between 10 AM to 4 pm from April to October and UVA present equally throughout daylight hours and throughout seasons both types of UV rays can cause skin cancer because they damage skin cells and alter their DNA, and also causes premature aging of the skin. A novel weave structure and denier (related to thread count per inch) may provide the sun protective properties. nowadays textiles and fabrics used for sun protective clothing are pre-treated with chemically modified UV- inhibiting ingredients during manufacturing to enhance their effectiveness, here in this paper author tried to use some environment-friendly natural ingredients as an alternative to chemically modified UV-inhibiting ingredients. All-natural ingredients from herbs like green tea leaf, pudina, and neem leaf extracts are used and experimental findings related to UPF(Ultraviolet protection factor) are discussed.